HUBUNGAN PERKEMBANGAN LAHAN TERBANGUN PERKOTAAN DENGAN FENOMENA IKLIM MIKRO URBAN HEAT ISLAND (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2017)
The micro climatic in environment of urban has happen as phenomenon urban heat island, some factor be the reasons involved at phenomenon. Remote sensing technology thermal channel, that very use full to investigate process urban heat island across the urban development. Propose of the research (1) Identify the development built up in city and relationships, vegetation and land surface temperature; (2) relationship of urban development, vegetation to urban heat island. Based raster micro structure cells it’s combination remote sensing data and GIS to understanding correlation one each other, in the statistical analyst of urban development, vegetation density, to land surface temperature. In the urban area with the high value in urban index have positive correlation with temperature changes, and low value vegetation index negative correlation with urban temperature, and population. The vegetation as natural ecology area can to holding on the temperature changes. It can do mention the phenomenon urban heat island across the urban phenomenon have relation very strong to micro climatic change.